Ukuran Perusahaan Memoderasi Pengaruh Perencanaan Pajak, Tunneling Incentive, dan Aset Tidak Berwujud terhadap Transfer Pricing - Eko Sudarmanto; Reni Anggraeni; Toto Sugihyanto; Fahry Reza; Laras Amarita (Universitas Muhammadiyah Palembang, 2025)
This study aims to determine the influence of Tax Planning, Tunneling Incentive, and Intangible Assets on Transfer Pricing Behavior with Firm Size as a Moderating Variable. The study adopts a quantitative approach with a sample of 7 companies in the automotive subsector of manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The sampling technique used is purposive sampling, utilizing Eviews 12 software. The method of analysis employed is panel data regression analysis. The partial results of the study show that the tax planning variable affects transfer pricing, the tunneling incentive variable does not affect transfer pricing, the intangible asset variable does not affect transfer pricing, firm size is able to moderate (strengthen) the effect of tax planning on transfer pricing, firm size is not able to moderate (strengthen) the effect of tunneling incentive on transfer pricing, and firm size is not able to moderate (strengthen) the effect of intangible assets on transfer pricing.